Pay TV Product quality and customer satisfaction: An investigation - Chidinma Udeh; Chukwudi Ifekanandu; Edwin Idoko; Chidera Ugwuanyi; Chioma Okeke (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The pay TV service sector in Nigeria is growing rapidly as new entrants are joining the market and consumers are adopting several brands to suit their needs. This implies a high rate of competition among the service providers to win over customer and expand their market share. The main objective of this study is to examine the effects of product quality on Pay TV customer satisfaction. The study used a survey research design and sampled 397 Pay TV subscribers. A total of 241 copies of the questionnaire were returned and the study hypotheses were tested using the multiple regression analysis. The study findings revealed that content quality, reception quality, and customer service has a positive and significant relationship and impact on Pay TV customer satisfaction. The study recommends that to increase the level of customer satisfaction and win the competitive war, operators in the pay TV service sector should improve their customer service unit, improve the stability of reception irrespective of weather conditions, maintain unique, educative and entertaining contents to stay ahead of competition while maintaining a competitive price.